Drip loss assessment by standard bag and filter paper wetness method and their relationships with broiler chicken meat quality classification - Sarkar, RR; Jahan, I; Sarker, T; Deen, RA; Ghosh, D; Akther, S; Hashem, MA (Meat Research, 2024)
This study investigates the effectiveness of two methods— the standard bag method and filter paper wetness (FPW) method—in assessing drip loss (DL) and their potential application in broiler chicken meat quality classification. The standard bag method measures drip loss by suspending meat samples in plastic bags to capture expelled fluids over a set period, whereas the filter paper wetness method involves pressing the meat onto filter paper to evaluate the amount of moisture released. In this study, samples from broiler chickens were assessed using both methods, and the resulting drip loss values were compared against meat quality categories such as PSE (pale, soft, exudative), normal, and DFD (dark, firm, dry) classifications. Both methods are widely used for evaluating drip loss, but their reliability and correlation with meat quality classification have not been extensively compared. Thirty broiler chickens were selected, and their breast meat was evaluated to understand the relationships between water-holding capacity (WHC), pH, lightness (L*), and other meat quality attributes. To facilitate this analysis, samples were categorized into three meat quality classes: Pale, Soft, and Exudative (PSE); Normal; and Dark, Firm, and Dry (DFD). The study aimed to assess the correlation between WHC and other evaluated characteristics and employed linear regression analyses to examine FPW and WHC as functions of 24-hour drip loss. Results showed that 5% DL corresponded to 64.77 mg water in FPW and was equivalent to 93.61% in WHC, establishing benchmarks for broiler meat quality classification. Using these 5% DL equivalents (93.61% WHC), along with immediate pH and lightness criteria, samples were accurately categorized across all quality classes. The high R² values (R 2 = 0.83, and P < 0.0001.) observed between WHC (%) and DL (%), as well as between FPW (mg) and DL (%) (R 2 = 0.82, and P < 0.0001.), underscored the reliability of these assessment methods. This study supports the efficacy of using WHC and FPW in the classification of broiler chicken meat quality, providing a reliable and quantifiable approach to meat quality evaluation. These findings have significant implications for meat industry practices, enabling precise classification and enhancing quality control in poultry meat production.